Hums in the humus: opportunities and challenges for soil ecoacoustics - Alex F. Taylor; Martin F. Breed; Carlos Abrahams; Amy Annells; Tom Bradfer-Lawrence; Timothy Cavagnaro; Carolyn-Monika Görres; Martin M. Gossner; Craig Liddicoat; Simon Linke; Oliver C. Metcalf; Louise Roberts; et al. (Trends in Ecology & Evolution, 2026)

Conservation planning for environmental water to climate refugia in the manageable Murray–Darling Basin - Joanne M. Bennett; Simon Linke; Shane Brooks; Alex Bush; James Hitchcock; Carmel Pollino; Ross M. Thompson (Journal of Environmental Management, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Species-level dataset is required for setting biodiversity conservation priorities for freshwater macroinvertebrates in Melbourne streams - Edward Tsyrlin; Melissa Carew; Ary A. Hoffmann; Simon Linke; Rhys A. Coleman (Journal of Environmental Management, 2023)

Global forest restoration opportunities to foster coral reef conservation - Andrés F. Suárez‐Castro; Hawthorne L. Beyer; Caitlin D. Kuempel; Simon Linke; Pasquale Borrelli; Ove Hoegh‐Guldberg (Global Change Biology, 2021)
Sediment runoff from disturbed coastal catchments is a major threat to marine ecosystems. Understanding where sediments are produced and where they are delivered enables managers to design more effective strategies for improving water quality. A management strategy is targeted restoration of degraded terrestrial areas, as it provides opportunities to reduce land‐based runoff from coastal areas and consequently foster coral reef conservation. To do this strategically, a systematic approach is needed to identify watersheds where restoration actions will provide the highest conservation benefits for coral reefs. Here, we develop a systematic approach for identifying global forest restoration opportunities that would also result in large decreases in the flux of sediments to coral reefs. We estimate how land‐use change affects sediment runoff globally using high‐resolution spatial data and determine the subsequent risk of sediment exposure on coral reefs using a diffusion‐based ocean transport model. Our results reveal that sediment export is a major issue affecting 41% of coral reefs globally. The main coastal watersheds with the highest sediment export are predominantly located in Southeast Asian countries, with Indonesia and the Philippines accounting for 52% of the sediment export in coastal areas near coral reefs. We show how restoring forest across multiple watersheds could help to reduce sediment export to 63,000 km 2 of coral reefs. Although reforestation opportunities in areas that discharge onto coral reefs are relatively small across watersheds, it is possible to achieve large sediment reduction benefits by strategically targeting watersheds located in regions with a high density of corals near to the coast. Thus, reforestation benefits on coral reefs do not necessarily come from the watersheds that produce the highest sediment export. These analyses are key for generating informed action to support both international conservation policy and national restoration activities.

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

Optimal allocation of Red List assessments to guide conservation of biodiversity in a rapidly changing world - Virgilio Hermoso; Stephanie Renee Januchowski‐Hartley; Simon Linke; David Dudgeon; Paulo Petry; Peter McIntyre (Global Change Biology, 2017)
The IUCN Red List is the most extensive source of conservation status assessments for species worldwide, but important gaps in coverage remain. Here, we demonstrate the use of a spatial prioritization approach to efficiently prioritize species assessments to achieve increased and up‐to‐date coverage efficiently. We focus on freshwater fishes, which constitute a significant portion of vertebrate diversity, although comprehensive assessments are available for only 46% of species. We used marxan to identify ecoregions for future assessments that maximize the coverage of species while accounting for anthropogenic stress. We identified a set of priority regions that would help assess one‐third (ca 4000 species) of all freshwater fishes in need of assessment by 2020. Such assessments could be achieved without increasing current investment levels. Our approach is suitable for any taxon and can help ensure that species threat assessments are sufficiently complete to guide global conservation efforts in a rapidly changing world.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Assessing the risks and opportunities of presence‐only data for conservation planning - Virgilio Hermoso; Mark J. Kennard; Simon Linke (Journal of Biogeography, 2015)
Aim Presence‐only data represent a significant source of information for quantifying biodiversity distributions and provide opportunities for use in conservation planning. The large databases of presence‐only records that are available and the lower cost of acquisition could help overcome the traditional problem of lack of data for conservation. However, there are risks associated with the use of presence‐only data inherent with the lack of true absences that might cause omission errors (species are erroneously thought to be absent) and loss of efficiency (more areas are thought to be necessary than needed). These errors could constrain the economic viability of conservation plans and thus the success of conservation practice. We therefore evaluated the opportunities and risks of using presence‐only data for conservation planning. Location Northern Australia. Methods The effects of using two different types (presence‐only and presence–absence) and different quantities of data were simulated by building predictive models on different subsets of data with increasing numbers of presence–absence or presence‐only records or a combination of both, for 80 freshwater fish species. We then compared the performance of conservation planning outcomes with the best information attainable (a true model built on the complete set of presence–absence data). We measured omission and commission errors in conservation planning outcomes, and the efficiency of and return on the investment in data acquisition. Results Including presence‐only data helped reduce commission and omission errors in conservation planning outcomes, but only when used in combination with at least some presence–absence data. The use of just a large quantity of presence‐only data resulted in significant reductions in the efficiency of conservation planning outcomes, as more areas than actually needed were required to achieve conservation targets. This reduction in efficiency was mainly related to inflated omission errors. Main conclusions We recommend using presence‐only data cautiously if this is the only source of data available; whenever possible, presence‐only data should be complemented with presence–absence data.

Relationship of fish and macroinvertebrate assemblages to environmental factors: implications for community concordance - Dana M. Infante; J. David Allan; Simon Linke; Richard H. Norris (Hydrobiologia, 2009)

Local stream habitat variables predicted from catchment scale characteristics are useful for predicting fish distribution - James Mugodo; Mark Kennard; Peter Liston; Sue Nichols; Simon Linke; Richard H. Norris; Mark Lintermans (Hydrobiologia, 2006)

Biodiversity: bridging the gap between condition and conservation - Simon Linke; Richard Norris (Hydrobiologia, 2003)